2007
DOI: 10.1111/j.1365-294x.2007.03262.x
|View full text |Cite
|
Sign up to set email alerts
|

From the Apennines to the Alps: colonization genetics of the naturally expanding Italian wolf (Canis lupus) population

Abstract: Wolves in Italy strongly declined in the past and were confined south of the Alps since the turn of the last century, reduced in the 1970s to approximately 100 individuals surviving in two fragmented subpopulations in the central-southern Apennines. The Italian wolves are presently expanding in the Apennines, and started to recolonize the western Alps in Italy, France and Switzerland about 16 years ago. In this study, we used a population genetic approach to elucidate some aspects of the wolf recolonization pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
157
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 155 publications
(177 citation statements)
references
References 58 publications
16
157
2
2
Order By: Relevance
“…All of these wolves were males which hunted in north-eastern and south-eastern Lithuania, and they carried rare haplotypes (W3-LT and W5-LT). Malebiased migration of wolves was also observed between the Alps and north Apennines [53]. The presence of immigrants might explain a linkage disequilibrium found in a few pairs of loci and slight deviation from HardyWeinberg equilibrium.…”
mentioning
confidence: 84%
“…All of these wolves were males which hunted in north-eastern and south-eastern Lithuania, and they carried rare haplotypes (W3-LT and W5-LT). Malebiased migration of wolves was also observed between the Alps and north Apennines [53]. The presence of immigrants might explain a linkage disequilibrium found in a few pairs of loci and slight deviation from HardyWeinberg equilibrium.…”
mentioning
confidence: 84%
“…Field data on radio-collared wolves show slight or no difference in dispersal patterns between sexes (Mech 1987;Gese and Mech 1991;Kojola et al 2006), whereas male-biased dispersal is suggested by genetic investigations carried out in North America and Europe (Lehman et al 1992;Seddon et al 2005;Fabbri et al 2007;Vonholdt et al 2008).…”
Section: Introductionmentioning
confidence: 92%
“…4; Hewitt 1996). Italy and Spain were among the most divergent populations (Italy: mean F ST = 0.15, Spain: mean F ST = 0.11) (Supplemental Table S3C), which likely reflect historic Ice Age isolation as well as drift from recent population contractions (Randi and Lucchini 2002;Lucchini et al 2004;Fabbri et al 2007;Gray et al 2009). Other genetically distinct populations include Eastern and Northern Europe, China, the Middle East, and Southwest Asia (Fig.…”
Section: Discussion Population Subdivision and Relationships Of Wolf-mentioning
confidence: 99%